Non-formal education of future physical education specialists in the university education system - Skrypchenko, Iryna; Hasan, Kasap (Національний технічний університет "Харківський політехнічний інститут", 2025)
Non-formal education in the training of future specialists in physical culture and sports may be carried out using various educational platforms, which includes the course. The proposed free educational courses will increase the level of competence of students at each course of study at the university.
Keywords: modern conditions; specialists; university education system; competence of students; physical education; educational platforms